Social and financial performance of the SIKAP microfinance program the case of woven-borrowers in a rural village in the Philippines - Jimena, C. G.; Balatibat, E. M.; Visco, E. S.; Amparo, J. S. (2003)
The study looked into the financial performance of SIKAP BIDANI Development Foundation, Inc. (SBDFI) Program of the organizational level and further attempted to analyze the organization's social performance by looking into socio-economic effects o SBDFI Microfinance Program at the borrower's level. It was focused on one of the program's pioneer areas in Buenavista, Magdalena, Laguna, Philippines. Results showed a 6.3 over-all point score out of a possible total score of seven (7) in its over-all performance. This means that the institution in general terms is considered very satisfactory with some improvements needed in areas identified by the performance standards. In terms of social performance, indicators showed that member-borrowers improved their livelihood and vulnerability to financial stress through the credit assistance given by SBDFI. Recommended areas for improvement are the development of new loan products and services and innovative methodologies for better and faster monitoring of the data required in their operations.
Keywords: Microfinance; Financial performance